2017
DOI: 10.1099/mgen.0.000140
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative analysis of the Burkholderia cenocepacia K56-2 essential genome reveals cell envelope functions that are uniquely required for survival in species of the genus Burkholderia

Abstract: Burkholderia cenocepacia K56-2 belongs to the Burkholderia cepacia complex, a group of Gram-negative opportunistic pathogens that have large and dynamic genomes. In this work, we identified the essential genome of B. cenocepacia K56-2 using high-density transposon mutagenesis and insertion site sequencing (Tn-seq circle). We constructed a library of one million transposon mutants and identified the transposon insertions at an average of one insertion per 27 bp. The probability of gene essentiality was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 105 publications
7
57
0
Order By: Relevance
“…The inability to generate DogcA suggests that absence of this gene may be deleterious for bacterial cell viability. This interpretation is consistent with previous Tn-Seq analysis showing that insertions are unrepresented within the B. cenocepacia ogcA (40) and with a report indicating the B. pseudomallei K96243 ogcA homologue (BPSL2668) is essential for survival (41). It is likely that without the terminal Gal the incomplete O-linked disaccharide glycan cannot be either effectively translocated across the membrane or processed by PglL, leading in both cases to the accumulation of Und-PP that cannot be recycled thus becoming growth limiting.…”
Section: Discussionsupporting
confidence: 93%
“…The inability to generate DogcA suggests that absence of this gene may be deleterious for bacterial cell viability. This interpretation is consistent with previous Tn-Seq analysis showing that insertions are unrepresented within the B. cenocepacia ogcA (40) and with a report indicating the B. pseudomallei K96243 ogcA homologue (BPSL2668) is essential for survival (41). It is likely that without the terminal Gal the incomplete O-linked disaccharide glycan cannot be either effectively translocated across the membrane or processed by PglL, leading in both cases to the accumulation of Und-PP that cannot be recycled thus becoming growth limiting.…”
Section: Discussionsupporting
confidence: 93%
“…As O -antigen production is thought to be not required for B. cenocepacia viability, Hanuszkiewicz et al (2014) raised the possibility that RmlB is involved in the biosynthesis of other nucleotide sugars that may play an essential role in a yet unknown metabolic pathway in strain K56-2. The essentiality of rmlB in strain K56-2 is further supported by a recent Tn-seq study ( Gislason et al, 2017 ), which also identified distinct sets of genes that are uniquely essential in K56-2 and J2315. Nonetheless, while disruption of J2315 rmlB in our study did not affect mutant accumulation in the worm in a single-strain infection experiment, abolishment of RmlB led to reduced killing of C. elegans .…”
Section: Discussionmentioning
confidence: 61%
“…Previously, we developed a high-density transposon mutant (HDTM) library in B. cenocepacia K56-2 by delivering a transposon element containing an outward rhamnose-inducible promoter ( P r haB ) into the genome ( 14 ). Using an enrichment process to isolate mutants in which P r haB is driving the expression of essential genes, we built a redundant knockdown library of 830 clones.…”
Section: Resultsmentioning
confidence: 99%